2007
DOI: 10.1038/sj.bmt.1705910
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive therapy with ganciclovir 5 mg/kg once daily for cytomegalovirus infection after unrelated cord blood transplantation

Abstract: The efficacy and safety of preemptive therapy using ganciclovir (GCV) 5 mg/kg once daily for CMV infection after unrelated cord blood transplantation (CBT) were studied. The initial preemptive therapy with GCV 5 mg/kg once daily led to resolution of CMV antigenemia in 25 of 34 patients (74%). In the remaining 9 patients (26%), antigenemia resolved after dose-escalation of GCV or change to foscarnet therapy. Recurrence of antigenemia was seen in 18 patients (53%). A total of 12 patients received the second pree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 18 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…Among CMV-seropositive recipients who do not receive antiviral prophylaxis, the rate of CMV infection after CBT is 40% to 80%, with one study reporting 100%. 9498 When patients receive prophylaxis with high-dose valacyclovir after CBT, it does not seem that CBT entails a significantly greater risk of CMV infection and disease than does peripheral blood stem cell or bone marrow transplantation. 89 …”
Section: Risk Factorsmentioning
confidence: 99%
“…Among CMV-seropositive recipients who do not receive antiviral prophylaxis, the rate of CMV infection after CBT is 40% to 80%, with one study reporting 100%. 9498 When patients receive prophylaxis with high-dose valacyclovir after CBT, it does not seem that CBT entails a significantly greater risk of CMV infection and disease than does peripheral blood stem cell or bone marrow transplantation. 89 …”
Section: Risk Factorsmentioning
confidence: 99%
“…One study described successful preemptive treatment with ganciclovir, 98 whereas another combined high-dose valacyclovir prophylaxis with continued monitoring and preemptive therapy. 89 …”
Section: Special Populationsmentioning
confidence: 99%
“…Among CMV-seropositive recipients who do not receive antiviral prophylaxis, the rate of CMV infection after CBT is 40% to 80%, with one study reporting 100%. [94][95][96][97][98] When patients receive prophylaxis with high-dose valacyclovir after CBT, it does not seem that CBT entails a significantly greater risk of CMV infection and disease than does peripheral blood stem cell or bone marrow transplantation. 89 Alemtuzumab is an anti-CD52 monoclonal antibody that results in CD41 and CD81 lymphopenia that can last for up to 9 months after administration.…”
mentioning
confidence: 99%
“…Recent studies of adults undergoing HSCT have shown that halving GCV dosage is a promising strategy for preemptive treatment of CMV infection . However, no corresponding studies have been performed in pediatric patients as yet.…”
Section: Discussionmentioning
confidence: 99%